Predominance of canine parvovirus type 2b in dogs of Ulaanbaatar City (Mongolian Journal of Agricultural Sciences, 2015)
Canine parvovirus is a highly contagious virus that causes fatal disease acute hemorrhagic enteritis and myocarditis in dogs. The aim of this work is to detect canine parvovirus 2 (CPV-2) by standard polymerase chain reaction (PCR). Viral DNA was isolated from faecel samples of 36 puppies with suspicious symptoms for parvovirus infection and used as template in standard PCR. 23 samples wereof CPV-2b serotype, 9 samples of CPV-2a serotype but 4 samples were neither 2b and nor 2a. We used two different primer sets, one specific both serotypes CPV-2a and CPV-2b and one specific only for CPV-2b. This allowed us to differentiate serotypes from each other. The further extension of this work will be essential for the epidemiology, viral evolution and phylogenetic studies of the mongolian domestic canine, cats and wild carnivores.Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 71-74